The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1093/genetics/142.3.717
|View full text |Cite
|
Sign up to set email alerts
|

3′ → 5′ Exonucleases of DNA Polymerases ϵ and δ Correct Base Analog Induced DNA Replication Errors on Opposite DNA Strands in Saccharomyces cerevisiae

Abstract: The base analog 6-N-hydroxylaminopurine (HAP) induces bidirectional GC → AT and AT → GC transitions that are enhanced in DNA polymerase ϵ and δ 3′ → 5′ exonuclease-deficient yeast mutants, pol2-4 and pol3-01, respectively. We have constructed a set of isogenic strains to determine whether the DNA polymerases δ and ϵ contribute equally to proofreading of replication errors provoked by HAP during leading and lagging strand DNA synthesis. Site-specific GC → AT and AT → GC transitions in a Pol→, pol2-4 or pol3-01 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Thus, both Orc1p and igin DNA was strikingly similar to that mediated by Pol⑀-HA (Figure 6). At the start of replication, all three proteins one strand of the DNA (Sugino, 1995;Shcherbakova and Pavlov, 1996;Zlotkin et al, 1996). To monitor the began to dissociate from origin DNA and became associated first with nonorigin DNA 8 kb distant from either progress of a replication fork, we analyzed the temporal association of DNA Pol⑀ with DNA sequences spanning origin (305 ϩ 8 kb and 306 ϩ 8 kb) and subsequently with the more distal sequence (17 kb; Figure 6).…”
Section: Proteins Are Components Of the Prereplicative Complexmentioning
confidence: 99%
“…Thus, both Orc1p and igin DNA was strikingly similar to that mediated by Pol⑀-HA (Figure 6). At the start of replication, all three proteins one strand of the DNA (Sugino, 1995;Shcherbakova and Pavlov, 1996;Zlotkin et al, 1996). To monitor the began to dissociate from origin DNA and became associated first with nonorigin DNA 8 kb distant from either progress of a replication fork, we analyzed the temporal association of DNA Pol⑀ with DNA sequences spanning origin (305 ϩ 8 kb and 306 ϩ 8 kb) and subsequently with the more distal sequence (17 kb; Figure 6).…”
Section: Proteins Are Components Of the Prereplicative Complexmentioning
confidence: 99%
“…Model organisms have provided important insights into the role that Pol ε infidelity plays in mutagenesis and tumorigenesis. Studies in yeast have shown that mutation rates are elevated in haploid and diploid strains carrying mutant Pol ε alleles that cause inactivated exonuclease activity (Morrison et al, 1991(Morrison et al, , 1993Morrison and Sugino, 1994;Ohya et al, 2002;Shcherbakova and Pavlov, 1996;Tran et al, 1999). As mutation rates increase, cells can adapt by evolving ways of suppressing this mutagenesis (Dennis et al, 2017;Herr et al, 2011b;Williams et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Polymerases d and 3, together with polymerase a (primase), are essential replicative enzymes functioning at DNA replication forks [5]. Point mutations that selectively inactivate the exonuclease domains of polymerases d or 3 confer mutator phenotypes in yeast [6] and mammalian cells [7], and there is good evidence that these exonucleases correct replication errors on opposite DNA strands [8]. It is not clear, however, whether polymerases d and 3 correct only their own errors.…”
mentioning
confidence: 99%